An in situ neutron diffraction study of plastic deformation in a Cu46.5Zr46.5Al7 bulk metallic glass composite. (August 2018) - Wang, D.M.; Chen, Y.; Mu, J.; Zhu, Z.W.; Zhang, H.F.; Wang, Y.D.; An, K.
Abstract: Micro-mechanical behaviors of a Cu46.5 Zr46.5 Al7 bulk metallic glass composite in the plastic regime were investigated by continuous in situ neutron diffraction during compression. Three stages of the plastic deformation were observed according to the work-hardening rate. The underlying natures of the work hardening, correlating with the lattice/microscopic strain evolution, are revealed for the three stages: (1) the initiation of shear bands, (2) the phase load transferring from the amorphous phase to the B2 phase and (3) the accelerated martensitic transformation and the work hardening of the polycrystalline phases promoted by the rapid propagation of the shear bands. Graphical abstract: Unlabelled Image